2020
DOI: 10.21203/rs.2.20642/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Different screening frequencies of carbapenem-resistant Enterobacteriaceae in patients undergoing hematopoietic stem cell transplantation: which one is better?

Abstract: Background A consensus has been reached that carbapenem-resistant Enterobacteriaceae (CRE) screening in immunosuppressed individuals can reduce the incidence of CRE bloodstream infection (BSI). Methods We retrospectively studied the clinical data of 395 consecutive HSCT patients from September 2017 to April 2019. From September 2017 to June 2018 (period 1), 200 patients received single CRE screening before transplantation. From July 2018 to April 2019 (period 2), 195 patients received continuous weekly CRE scr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…21 The incidence of CRE infection in HCT recipients ranges from 1.6% to 3.4%. [22][23][24] Prior colonisation by CRE dramatically increases the CRE BSI rates in the post-HCT period. 3,16,25 While Klebsiella pneumoniae carbapenemase (KPC) is the most common CRE subtype isolated from bacteraemic HCT recipients, oxacillinase (OXA-48) and New Delhi metallo-β-lactamase (NDM) producing CREs are increasingly being reported.…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 The incidence of CRE infection in HCT recipients ranges from 1.6% to 3.4%. [22][23][24] Prior colonisation by CRE dramatically increases the CRE BSI rates in the post-HCT period. 3,16,25 While Klebsiella pneumoniae carbapenemase (KPC) is the most common CRE subtype isolated from bacteraemic HCT recipients, oxacillinase (OXA-48) and New Delhi metallo-β-lactamase (NDM) producing CREs are increasingly being reported.…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…A regular and continuous screening strategy via faecal culture has been found to be more effective for detection for CRE carriage compared with onetime screening strategy. 24 Forcina et al 23 reported substantial reduction in mortality due to carbapenem-resistant Klebsiella pneumoniae (CRKp) BSI at 1 year post-HCT when weekly surveillance cultures strategy was employed, with contact precautions, in carriers and early targeted therapy was initiated in febrile neutropenic carriers. The 2015 Italian multidisciplinary consensus statement on CRKp infection management in HCT recipients recommended monitoring for CRE colonisation before hospital admission for HCT, weekly post-HCT monitoring in the event of CRKp isolation from other patients in the same BMT unit and in patients who present with post-HCT intestinal complications, in particular GVHD.…”
Section: Gastrointestinal Screening For Cre Colonisation Before Hctmentioning
confidence: 99%